2018
DOI: 10.5334/ijic.3106
|View full text |Cite
|
Sign up to set email alerts
|

Translating the Elements of Health Governance for Integrated Care from Theory to Practice: A Case Study Approach

Abstract: Introduction:Against a paucity of evidence, a model describing elements of health governance best suited to achieving integrated care internationally was developed. The aim of this study was to explore how health meso-level organisations used, or planned to use, the governance elements.Methods:A case study design was used to offer two contrasting contexts of health governance. Semi-structured interviews were conducted with participants who held senior governance roles. Data were thematically analysed to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…Evaluations of individual programmes also reflect the importance of proactive management to successful implementation [e.g. [14][15][16][17]. Contributions of strategic managers that have been identified to date are bringing together stakeholders, mobilizing action within organisations by emotionally connecting individuals with their vision, securing internal and external resources for implementation including to support learning, fostering a culture of innovation, and prioritising involvement of communities within strategic developments [12,13,15,17,54].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluations of individual programmes also reflect the importance of proactive management to successful implementation [e.g. [14][15][16][17]. Contributions of strategic managers that have been identified to date are bringing together stakeholders, mobilizing action within organisations by emotionally connecting individuals with their vision, securing internal and external resources for implementation including to support learning, fostering a culture of innovation, and prioritising involvement of communities within strategic developments [12,13,15,17,54].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17]. Contributions of strategic managers that have been identified to date are bringing together stakeholders, mobilizing action within organisations by emotionally connecting individuals with their vision, securing internal and external resources for implementation including to support learning, fostering a culture of innovation, and prioritising involvement of communities within strategic developments [12,13,15,17,54]. Operational managers' contribution includes generating confidence within frontline staff of their ability to implement, communicating the overall vision in a version that is understandable by the frontline, quantifying tangible benefits for service recipients, and practical coordination of activities and resources [1,4,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In complex health systems, this focus on implementation research provides a basis for 'context-specific and evidence informed decision-making' regarding translation of theory into practice (Peters et al, 2013). The research in this thesis has resulted in a number of international and national publications (Nicholson et al, 2012;Nicholson et al, 2013;Nicholson et al, 2014;Nicholson et al, 2018), peer reviewed presentations (see Appendix 4), invited presentations, collegial meetings and training forums. In addition to the publications and peer reviewed presentations, the following section describes how the research has been presented to inform health policy and turn demonstrated research evidence into practice.…”
Section: Knowledge Translationmentioning
confidence: 99%
“…Leadership was a key enabler identified in both the alliances in NZ (Gauld, 2017) and integrated care services (Charles et al, 2018;Nicholson et al, 2018). Health care systems are complex systems in which innovation is accompanied by a degree of variation (Kelley-Patterson, 2012).…”
Section: Future Researchmentioning
confidence: 99%